SUPLEMENTASI BESI MINGGUAN MENINGKATKAN HEMOGLOBIN SAMA EFEKTIF DENGAN KOMBINASI MINGGUAN DAN HARIAN PADA REMAJA PUTRI - Sutanti, Yeti; Briawan, Dodik; Martianto, Drajat (Jurnal Gizi dan Pangan, 2016)
The objective of this quasi experimental study was to analyze effectiveness of three iron supplementation on hemoglobin concentration of adolescent girls. Three intervention groups have received iron supplements (60 mg of iron elemental and 0.25 mg folic acid) for 14 weeks in March-June 2015 in Tasikmalaya District. The groups received supplementation weekly (M), weekly and daily for ten days during menstruation period (M+Mens), and weekly and nutrition education (M+PG) supplementation respectively. The result showed that the mean change of hemoglobin was not significantly different among the three groups (M+PG 0.63±1.16 g/dl, M+Mens 0.48±1.04 g/dl, and M 0.44±1.13 g/dl) (p>0.05). Iron supplementation could reduce the prevalence of anaemia by 15.8% (M), 18.0% (M+Mens), and 4.9% (M+PG). Weekly iron supplementation was as effective as weekly and daily during menstruation period on hemoglobin change among adolescent girls. Iron supplementation in adolescent is better done intermittently (weekly) with benefit addition the high compliance in supplement consumption.Keywords: adolescent, anaemia, hemoglobin, iron supplementation